KOMPOSISI SERANGGA TANAH PADA KEBUN KARET DI NAGARI PADANG XI PUNGGASAN KECAMATAN LINGGO SARIBAGANTI KABUPATEN PESISIR SELATAN - Elisa, Fitri; Jasmi, Jasmi; Abizar, Abizar (Pendidikan Biologi, 2013)
ABSTRACTSoil insects are insects that live in the soil. Has done research about Soil Insects In rubber garden di Nagari Padang XI Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan which aims to determine the composition of Soil Insects In rubber garden di Nagari Padang XI Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir.This study from July 2013 to Agustus 2013 using the descriptive survey method. Sampling was done at two places namely rubber garden ±6 years old and the rubber garden ±10 years old. From the results of the study found the presence of an soil insects on the second place there are 2  orders consisting of 4 families, 4 genera and 5 species. Soil insects on the rubber garden ±10 years old found that the highest relative density is species Homodia cingula of 40,5% and a low relative density is species Holojayx diversiugis of 9,5%. The highest relative frequency is species Homodia cingula of 37,5% and the lowest relative frequency is speises Holojayx diversiugis of 10,3%. Highest density at age 10 is ± rubber plant species Holojayx diversiugis at 24,2% and the relative density of the lace is 15,8 species Isotoma viridis. The highest relative frequency is species Sminthurus incisus by 25,3% and the lowest relative frequency is speises Homodia sp. of 14,8%.